2016
DOI: 10.5430/jha.v5n2p47
|View full text |Cite
|
Sign up to set email alerts
|

The look and feel of resilience: A qualitative study of physicians’ perspectives

Abstract: Some physicians can effectively cope and thrive in the face of potentially stressful job conditions, while others experience serious, negative consequences. This ability to be resilient may improve physician wellness and benefit health care organizations, yet little is known about what resilience means to physicians. This paper explores how physicians understand resilience both as they observe it in their colleagues and as they experience it themselves. Semi-structured interviews were conducted with 32 physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Most FPs admitted to have experienced or come close to burnout at some point in their careers. These findings correspond with those of Polachek et al 42 who found that a difference exists between how physicians perceive resilience in themselves and what they observe in their colleagues. Specifically, FPs may hold unrealistic and unachievable expectations for their own resilience.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most FPs admitted to have experienced or come close to burnout at some point in their careers. These findings correspond with those of Polachek et al 42 who found that a difference exists between how physicians perceive resilience in themselves and what they observe in their colleagues. Specifically, FPs may hold unrealistic and unachievable expectations for their own resilience.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, FPs may hold unrealistic and unachievable expectations for their own resilience. 42 These unrealistic expectations are perpetuated within the professional culture of medicine which praises perfection, and unduly judges those who display vulnerability. 43 This serves to further highlight the need for cultivating resilience among FPs.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, this identity has shifted more towards stoicism (Brown 2019). In this climate, the onus often lands on individuals to negotiate stressful experiences in isolation (Polachek et al 2016). Compartmentalisation and resilience—being able to set aside or mask emotions—are spoken of as essential skills (Arnold-Forster 2020b), although there is no formal training in this area, nor do we fully understand if and how an individual can or should learn to compartmentalise.…”
Section: Classic Unidimensional Operationalisations Of Stressmentioning
confidence: 99%
“…Supporting its inclusion as a key professional competency, there is a growing recognition that resilience is an essential quality for social workers, as it has strong potential to help them manage the complexities of the job more effectively, enhance their decision-making capacities, adapt positively to the challenges of a constantly changing work environment, as well as protect their health and wellbeing (Collins, 2007;Wilks and Spivey, 2010;Beddoe et al 2011;Grant & Kinman, 2014;Kapoulitsas and Corcoran, 2014). There is little agreement on how to conceptualise resilience, but the characteristics and skills that help professionals cope, adapt and develop will, to a large extent, be dependent on the requirements of the job role (Rajan-Rankin, 2013;Authors, 2014;Polachek et al 2016). In order to enhance resilience in social work contexts, it is therefore crucial to gain an understanding of how this quality is perceived by workers, the personal and organisational resources that underpin it, and the strategies that have the potential to enhance it.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience has been defined in many ways, but the notion of positive adaptation to adversity, as well as the importance of control, coping and support, is a recurring theme (Fletcher and Sarkar, 2015;Polachek et al 2016). A study that explored the personal representations of resilience of 300 English social workers conducted by Grant and Kinman (2013) found considerable variation in how the concept was defined, but it was typically described as a dynamic interplay between personal characteristics and the effective utilisation of support from various sources.…”
Section: Introductionmentioning
confidence: 99%